Fluorometabolite biosynthesis: isotopically labelled glycerol incorporations into the antibiotic nucleocidin in Streptomyces calvus. Issue 1 (15th November 2016) - Bartholomé, Axel; Janso, Jeffrey E.; Reilly, Usa; O'Hagan, David
Abstract : The pattern of isotope incorporations into the fluorometabolite nucleocidin is explored in Streptomyces calvus from selectively labelled glycerols. Abstract : Deuterium and carbon-13 labelled glycerols have been fed to Streptomyces calvus fermentations and isotope incorporation into the fluorine containing antibiotic nucleocidin have been evaluated by 19 F-NMR. A single deuterium atom was incorporated from [ 2 H5 ]- and ( R )-[ 2 H2 ]-glycerol into C-5′ of the antibiotic, suggesting that an oxidation occurs at this carbon after ribose ring assembly from glycerol (pentose phosphate pathway), during nucleocidin biosynthesis.